Effects of external carbon sources on the quality and volatile components of kiwi wine - HUANG Xiaolan; HE Xufeng; XIONG Shuang; ZHANG Chunyi; ZHENG Rong (Shipin yu jixie)
ObjectiveIn order to optimize the fermentation process of kiwi wine and improve its overall quality, the effects of different exogenous carbon on its quality and volatile components were compared.MethodsSelected sucrose, glucose, maltose, brown sugar, high fructose corn syrup, glutinous rice and rice sacchacation solution as exogenous carbon, and adjusted the initial sugar content of fermentation solution to 23%. Biomass change, alcohol content, organic acid content, monomer phenol content, volatile components and sensory properties were measured.ResultsThe fermentation rate of maltose group was the slowest, the alcohol content was the lowest, and the organic acid accumulation was the least. The total amount of monomer phenols in brown sugar group was the highest, among which gallic acid (217.45 mg/L) was the highest monomer phenolic substance in all groups, which improved the antioxidant capacity and reduced the methanol content. In terms of aroma, a total of 53 volatile components were isolated and identified in the seven carbon source fermentation groups, and the average contents of alcohols (8.985 mg/kg) and esters (1.625 mg/kg) were the highest, accounting for 71.1% and 12.7%. The total volatile components of glucose group and high fructose syrup group were the highest, maltose group was the lowest, and brown sugar group was the highest.ConclusionIn summary, glucose, sucrose, high fructose corn syrup and brown sugar can be used as ideal external carbon sources for kiwi fermentation, and brown sugar can be further explored and applied.